The Modeling of SVC for the Voltage Control in Power System - Nor Adni Binti Mat Le; W Mohd Nazmi bin W Musa; Nurlida binti Ismail; Nurul Huda binti Ishak; Nur Ashida binti Salim (Institute of Advanced Engineering and Science, 2017)
One of the major causes of voltage instability in power system is the reactive power limit. Therefore, this paper aims to analyze the effect of Static Var Compensator (SVC) on voltage stability of a power system. There are many ways to control the voltage, but in this paper only focus on the SVC and IEEE-9 buses. The SVC circuit and IEEE-9 buses were designed and modelled in Power World. The Newton Raphson method was applied to compute the load flow solution. Then, the reactive power (Q) was injected to SVC and the effect of SVC on IEEE 9-buses were studied. The analysis of voltage control was considered the conditions of fault occurred at the bus. The simulation results obtained in Power World demonstrate that the improvement voltage in the IEEE 9-buses when the Q was injected into SVC circuit. Besides, the QV curve was plotted to show the sensitivity and variation bus voltages with respect to the Q injection.